Pengaruh Likuiditas, Profitabilitas, dan Leverage terhadap Nilai Perusahaan yang Dimoderasi oleh Kebijakan Dividen - Ade Wisnu Prasetya; Musdholifah Musdholifah (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
Company value is a long-term goal of the company which is used as a benchmark of company success. The purpose of this research is to analyze the influence of liquidity, profitability, and leverage towards company value with dividend policy as a moderating variable. The object of this research is companies in the Miscellaneous industry sector in 2014-2018. This type of research is a quantitative research and used secondary data which consists of an annual report on IDX. The sampling determined by using a purposive sampling method and produced 13 samples of companies. The analysis used a multiple linear regression and moderated regression analysis (MRA) method. The result of this study indicated that only profitability has a positive significant relation to company value. Liquidity is not significant because when a company can repay its debt with assets owned it does not reflect that the company is in good condition because it can occur when cash in the company is not used as well as possible. Then for leverage does not affect because companies use their capital rather than using debt. The dividend policy can moderate the relationship between liquidity and profitability to the value of the company. Dividend policy cannot moderate the relationship of leverage to the value of the company due to a prohibition on dividend payments with a reduction in company capital.